Agroclimatic characteristics, nutrient uptake, morphology, and yield of abaca plants (Musa textilis nee) which managed agroforestry in Ngawi - Najibunniam, Arly; Susila Putra, Eka Tarwaca; Kurniasih, Budiastuti (Jurnal Ilmu Pertanian, 2025)
This research aimed to measure microclimate characteristics,  evaluate abaca plants nutrient uptake, morphology and yield, and determine the optimal microclimate characteristics on abaca cultivation land managed using teak-based agroforestry in the middle and advanced phases in Ngawi. The research was arranged in a nested design. The parameters observed include agroclimatic characteristics, nutrient uptake, physiology and morphology, as well as yield of abaca plants. The middle phase of abaca-teak agroforestry shows higher humidity and lower temperatures than the advanced phase with a difference of 3% and 1.57ºC, respectively. This is because microclimate in the middle phase is more suitable due to the multistrata canopy structure and greater plant diversity. The absorption all of macro and micro nutrients in the middle phase was better than in the advanced phase, indicating that abaca in the middle phase had more nutrient uptake. The morphological traits of abaca in the middle phase were better and significantly different compared to those in the advanced phase, with the differences in plant height variables of 110.11 cm, apparent stem circumference of 7.99 cm, and number of suckers of 5. Furthermore, in terms of yield characteristics, all variables showed that abaca planted in the middle phase was better than the advanced phase, it can be seen the respective differences in the number of banana fronds is 4 blade, the weight of banana fronds is 2.95 kg/plant, the fresh weight of fiber is 353.66 g/plant, and the weight of dry fiber is 120.67 g/plant.